PENGARUH PEMBERIAN ASAP CAIR SERESAH DAUN KARET PADA SEMAI PULAI (Alstonia scholaris) DENGAN MEDIA TANAM BERKOMPOS - Rizal Efendi; M. Mardhiansyah; Rudianda Sulaeman (JURNAL ILMU-ILMU KEHUTANAN, 2019)
Alstonia scholaris is one of the plant indigenous and able to grow rapidly. In the application of fertilizer should be can improve the yields a plant including Alstonia scholaris. Solutions offered as used fertilizer local, the use of waste as fertilizer need to be improved. One of effective way is to take advantage of waste rubber (leaves) be the fertilizer the form of liquid smoke. The purpose of this research is to determine the growth seedling Alstonia scholaris by administering liquid smoke of litter leaves rubber as fertilizer liquid. This study conducted by the method of the Complete Random Design (CRD) with 4 treatment 3 times repeat with each experiment consist of 10 plants so obtained 120 units plants. The results that the application of liquid smoke influential growth seedling Alstonia scholaris dose is best P2 (3 ml/L water), by showing the result of 100% percent of life seedling, growt of plant height is 16,98 cm and dry weight of plant is 29,97 g.